African Elephant Specialist Group Chair report/ Rapport du Groupe de Spécialistes de l’Eléphant d’Afrique - Ben Okita-Ouma; Rob Slotow (Pachyderm)
As we moved into the new quadrennium, 2021–2024, we were hoping to build on the foundations developed during our tenure to date. Unfortunately, the Covid-19 epidemic significantly changed the landscape, effectively delaying the start of the new quadrennium and/or direct physical engagements and field visits due to travel and meeting restrictions. Regardless, we are very pleased to be able to continue to facilitate, coordinate and enable the work of the African Elephant Specialist Group (AfESG). As we entered the new quadrennium, we are fortunate to have the continued involvement of the existing membership, but also pleased that a number of new members have joined the Group. We have strengthened our membership through increased numbers, additional skillsets and by building collegiality with governments and multi-lateral agencies. Our nine working groups and task forces are poised to tackle some thirty odd targets, which we developed around our goals and aligned to the five key components of Assess, Plan, Act, Communicate and Network in the IUCN’s Species Strategic Plan.